Reproductive pattern comparison of Uca thayeri Rathbun, 1900 and U. uruguayensis Nobili, 1901 (Crustacea, Decapoda, Ocypodidae) - Costa,Tânia Marcia (2006)
Ovigerous females of Uca thayeri and U. uruguayensis were used to achieve and compare their reproductive pattern. The females mean size was 6.6 ± 0.8mm for U. uruguayensis and 17.3± 4.4mm for U. thayeri. The mean fecundity obtained for U. uruguayensis was 1883 ± 490 eggs (N = 27) and for U. thayeri was 31068 ± 11186 eggs (N = 31). The differences observed in reproductive pattern of U. thayeri and U. uruguayensis suggest an adaptive strategy by each species: U. thayeri presented seasonal reproduction with a pronounced intensity from January to March and higher fecundity, while U. uruguayensis reproduction was continuous all year round, but with lower fecundity.